Influence of amyloid and APOE on cognitive performance in a late middle-aged cohort - Mielke, Michelle M. (Alzheimers Dement, 2015)
INTRODUCTION: Few studies have examined the effects of amyloid and APOE genotype on cognition among middle-aged individuals. METHODS: We included 464 cognitively normal, test-naïve, participants with PiB-PET amyloid imaging, mean age of 62.7 (range 51–71 years), enrolled in the Mayo Clinic Study of Aging. Participants completed multiple cognitive assessments, including a standard neuropsychological battery and the CogState computerized battery, over 30 months of follow-up. Linear mixed models were used to examine the effects of amyloid and APOE genotype on baseline cognition and cognitive decline. RESULTS: Elevated amyloid was not associated with tests of episodic memory, but did predict declines on tests of executive function. APOE genotype was not associated with cognition. Among APOE ε4 non-carriers, higher amyloid was predictive of decline on tests of executive function and on one episodic memory test. DISCUSSION: Elevated amyloidosis and APOE genotype does not appear to exert a dramatic influence on cognition in middle-age.